Forever my girl - McLaughlin, Heidi (Romance fiction writer) (McLaughlin, Heidi (Romance fiction writer). Beaumont series, 2017)
"I was never supposed to be a rock star. I had all my life planned out for me. Play football in college. Go to the NFL. Marry my high school sweetheart and live happily ever after. I broke both our hearts that day I told her I was leaving. I was young. I made the right decision for me, but the wrong decision for us. I've poured my soul into music, but I've never forgotten her. Her smell, her smile. and now I'm going back. After ten years. I hope I can explain that after all this time. I still want her to be my forever girl"--Page [4] of cover.